1993
DOI: 10.1007/bf00357389
|View full text |Cite
|
Sign up to set email alerts
|

A new mode to excite a gas-discharge XeCl laser

Abstract: Abstract.The charge mode is a new mode to excite a discharge XeC1 laser based on the dynamics of a spikersustainer circuit with a magnetic pulse compressor. The breakdown voltage is higher than in any other mode, due to a very fast rise time. The higher breakdown voltage provides a wider discharge and we found that more energy can be deposited before discharge instabilities terminate the optical output. PACS: 42.55.GpThe efficiency of high-pressure, self-sustained, gas-discharge excited lasers, like excimers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We also investigated the performance of the pre-pulse-main-pulse circuit. This circuit, figure 5, can operate in two modes called the 'resonant overshoot' mode [13] and the 'charge' mode [15] respectively. 'Resonant overshoot' mode is obtained when the pre-pulse is triggered at about the reversal of the charging current.…”
Section: X-ray Pre-ionisation Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the performance of the pre-pulse-main-pulse circuit. This circuit, figure 5, can operate in two modes called the 'resonant overshoot' mode [13] and the 'charge' mode [15] respectively. 'Resonant overshoot' mode is obtained when the pre-pulse is triggered at about the reversal of the charging current.…”
Section: X-ray Pre-ionisation Sourcementioning
confidence: 99%
“…A number of electrical circuits and modes of operation has been studied during the course of the project [13,14,15]. Application of x-ray switching [16], where the pre pulse circuit and the main switch can be omitted simplifies the circuit significantly.…”
Section: X-ray Pre-ionisation Sourcementioning
confidence: 99%
“…2 shows the electrical circuit schematically. The laser could operate in the 'resonant overshoot mode' [6] and in the 'charge mode' [7]. The spiker circuit includes a one-step pulse compression circuit that has two functions: Firstly, it increases the rise time and duration of the current pulse through the spiker thyratron which helps to increase the life time of this thyratron at high repetition rate operation and secondly it plays an important role when the circuit operates in the charge mode.…”
Section: Experimental Configurationmentioning
confidence: 99%
“…3 that for charge-mode operation the discharge current starts a few tens of nanoseconds after the breakdown caused by the spiker pulse. This can be explained as follows [ 7,8] : The saturable inductors, L, and L,, are initially in the reversed saturated state caused by the PFN-charging current that still has a non-zero value. For charge mode operation it is essential that the spiker is fired a few hundred of nanoseconds -- before the charging current of the PFN capacitor, Q,,, crosses zero.…”
Section: Experimental Configurationmentioning
confidence: 99%
“…Here, the laser is operated by switch in the primary part of the pulser which handles much lower voltages, longer pulses and smaller energies. The successful operation of pulser sustainer TEA-CO 2 laser (Taylor & Lepold 1985Sylvan et al 1991) and excimer laser (Timmeraans et al 1993) using ASSE has been reported.…”
Section: Introductionmentioning
confidence: 99%